Graft Copolymerization of Vinyltriethoxysilane Onto Deproteinized Natural Rubber - Nghiem, Thi Thuong; Nguyen, Van Dong; Phan, Trung Nghia; Kawahara, Seiichi (Old Journal, 2019)
In this work, graft copolymerization of vinyltriethoxysilane (VTES) onto deproteinized natural rubber (DPNR) was carried out to prepare in situ nanosilica reinforced natural rubber. Graft copolymerization of VTES onto DPNR was performed in latex stage with TBHP/TEPA as initiators with initiator concentrations of 0.033, 0.066 mol/kg-rubber and monomer concentrations of 1.05, 1.5 and 2.0 mol/kg-rubber. VTES conversion is derived from silica content which is determined by burning method. The graft copolymers were characterized by FT-IR and TEM. It was found that VTES conversion was about 80% and it is independent on initiator concentration. The high conversion is believed to be due to auto hydrolysis of ethoxy groups in aqueous solution and subsequent condensation to form in situ silica. Reinforcement effect of the in situ silica on DPNR is investigated in terms of tensile properties. The stress at break of in situ silica-reinforced natural rubber was about 3 times higher than that of non-reinforced natural rubber. TEM images show that the silica particles with the size less than 200 nm were well dispersed in NR matrix.